Efecto del clima en la reproducción del pino Paraná (Araucaria angustifolia): Pautas para el manejo de esta especie en peligro crítico de extinción - Latorre, Fabiana (2019)
Regeneration of Araucaria angustifolia on its original ambient has seen reduced over the last decades. So a comparative study of reproductive phases in two climatically different areas of Argentina was performed. Aerobiological surveys were carried out during 2015 in INTA plots of San Antonio (Misiones) and 25 de Mayo (Buenos Aires). The corresponding seeds to the pollination period studied were harvest during 2017. Differences in airborne pollen curves were detected. Pollen and seed productions were higher in the temperate region associated to differences in temperatures during different phases. Guidelines for conservation of this native forestal species in risk were proposed.